3a + 4a +/- 6; take the 3a & 4a and combine them; 7a +/- 6 would be your answer as 6 cannot combine with 7a due to the variable. If 7a +/- 6 = 0, then subtract/add (respectively) the 6 depending on the operation. Therefore 7a + 6 = 0 turns to 7a = -6. Divide the 7 with the -6 to get the a alone; a = -6/7 or -0.8. Cannot be simplified.
7A + 3
(7a + 35)/-7 = 7(a + 5)/-7 = -(a + 5) = (-a - 5)
7a + 6 = -36 Subtract 6 from both sides: 7a = -42 Divide both sides by 7: a = -6 a = -6
a + 18 = 7a a-a +18 = 7a-a 18 = 6a 18/6 = 6a/6 3 = a 3=a
7(a-2b)-6(a-4b) 7a - 14b - 6a - 24b 7a - 6a - 14b - 24b a - 38b
7a
It is: 7a+1 when simplified
3a + 4a +/- 6; take the 3a & 4a and combine them; 7a +/- 6 would be your answer as 6 cannot combine with 7a due to the variable. If 7a +/- 6 = 0, then subtract/add (respectively) the 6 depending on the operation. Therefore 7a + 6 = 0 turns to 7a = -6. Divide the 7 with the -6 to get the a alone; a = -6/7 or -0.8. Cannot be simplified.
Oh, dude, it's like math time! So, when you add 3a and 7a together, you get 10a. It's like combining the apples and oranges of algebra. So, the simplified answer is just 10a. Easy peasy, lemon squeezy!
It can be simplified to: -45a-15
7A + 3
(7a + 35)/-7 = 7(a + 5)/-7 = -(a + 5) = (-a - 5)
7a + 6 = -36 Subtract 6 from both sides: 7a = -42 Divide both sides by 7: a = -6 a = -6
The variable is a. You can solve for it, like this: 8a - 9 = 7a - 6 8a = 7a + 3 8a - 7a = 3 a = 3
a + 18 = 7a a-a +18 = 7a-a 18 = 6a 18/6 = 6a/6 3 = a 3=a
To factorize the expression 7a^2 - 8ab, you need to find the greatest common factor of the two terms. In this case, the common factor is a. So, you can factor out an 'a' to get a(7a - 8b) as the factored form of the expression. This means that 7a^2 - 8ab can be simplified as a multiplied by the quantity (7a - 8b).